Draft Annual Plan 1995-96 Government of Mizoram - Planning Commission (Planning Commission, 1995)
Mizoram is situated between 20°20' and 24°27' North, 92°20' and 93°29' East, and covers an area of 21,081 sq. Kms. It is bounded on the North by the District of Cachar of Assam and the State of Manipur, on the east and South by Chin Hills of Myanmar, on the West by the Chittagong Hill Tracts of Bangladesh and the State of Tripura. The Tropic of Cancer runs through the State of Mizoram. Mizoram, therefore, occupies a very strategic position in the North Eastern corner of India.
Government of Mizoram, Planning and Programme Implementation Department